When Does Oil Harm Child Mortality?. (September 2021) - Bellinger, Nisha; Fails, Matthew D.
When is oil a curse for health outcomes? This paper addresses the question by analyzing the effect of oil wealth on child mortality rates in nondemocratic countries. We argue that oil is particularly likely to harm child mortality when leaders have short time horizons. Such leaders are more likely to use oil revenues to finance private goods and patronage which builds their support coalition at the expense of public goods that benefit the broader population. We test this argument using panel regression and a global sample of nondemocratic regimes, supplemented with a case study of Cameroon. Results from both empirical approaches are consistent with our argument. These findings identify some specific conditions under which oil can be detrimental to child mortality, and thus explain some of the variation in health outcomes across oil-producing states.